Current status of Ichthyofaunal diversity of Indravati Stream a Tributary of the Bhagirathi River in Uttarkashi - Deepak Rana; Nilay Singh; Madhu Thapliyal; Ashish Thapliyal (Environment Conservation Journal)
The present study evaluates the water quality, benthic diversity, and fish diversity of the Indravati Stream, a tributary of the Bhagirathi River in Uttarkashi, from January 2022 to December 2023. Significant spatial and temporal variations were observed in physicochemical parameters across three altitudinal sites. Water temperature ranged from 4.83°C to 18.13°C, pH remained slightly alkaline (7.14-7.38), and dissolved oxygen varied from 5.46 to 9.76 mg/L. Benthic analysis revealed 325 individuals across 6 orders and 12 families, dominated by Ephemeroptera, Trichoptera, and Diptera. Our study reveals a striking decline in fish diversity within the Indravati Stream, with only 6 out of the 11 species previously documented twelve years ago currently persisting, indicative of a severe crisis threatening the aquatic biodiversity of the region. Alarmingly, two species of the Mahseer, Tor tor (Data Deficient) and Tor putitora (Endangered), listed in the IUCN Red List of 2018, were absent during the investigation, underscoring the grave threat to the region's aquatic biodiversity. Uttarakhand is renowned for its rich diversity of water resources, yet the alarming situation observed in the Indravati Stream raises concerns about potential parallel declines in other water bodies across the region. These findings highlight the pressing need to develop comprehensive conservation strategies and implement sustainable management practices to mitigate the harmful impacts of environmental stressors and anthropogenic activities on the Indravati Stream and safeguard its aquatic ecosystem.